A 2D non-water substructure model in time domain for breakwater-water-bedrock (layered) system excited by inclined seismic waves. (15th October 2022) - Zhao, Mi; Su, Chengkun; Wang, Piguang; Song, Xiehong; Zhang, Chao
Abstract: The coastal structures, such as breakwaters and reefs, are usually vulnerable to the strong earthquake waves propagating through their bedrock foundation. This study proposes a 2D non-water substructure model in time domain for breakwater-water-bedrock (layered) (BWB) system, where the fluid-solid dynamic interaction is embodied by added mass and the equivalent seismic loading calculated from ocean free-field (without structure) accomplishes the inclined incidence of P or SV wave with any angle. Besides, the cutoff boundaries of the fluid are applied exact absorbing boundary conditions (ABCs) to simulate the far-field of water while the viscous-spring ABCs are employed to simulate the far-field of bedrock. Then, the accuracy of substructure method is verified by some numerical examples. However, the exact added mass matrix is fully populated and not easy to use for general software. Therefore, the simplified added mass models for water-bedrock system, water-structure system and BWB system are furtherly developed, including the relevant simplified formulas fitted by curve fitting method. Additionally, the numerical results indicate the good effectiveness of proposed model. Highlights: A 2D non-water substructure simplified model for BWB system under obliquely incident seismic waves is proposed. Simplified added mass models (2D) for water-bedrock and water-structure interaction are established. A simplified formula for correction factors of modified-lumped added mass is proposed.